Pengaruh Aktivitas Wisatawan Terhadap Keanekaragaman Tumbuhan Di Sulawesi - Regina Rosita Butarbutar; Soemarno Soemarno (Journal of Indonesian Tourism and Development Studies, 2013)
Tourist arrival and its effects on the sustainability of biodiversity in Sulawesi is one of the interesting public issues discussed at this time. Object of the most visited by tourists are protected forest ecotourism. In a protected forest tour are endemic plant and animal species that must be protected and preserved in order to sustain their ecosystem.  Forest ecosystem suggests the dynamic interactions between plants, animals, and microorganisms and their abiotic environment working together as a functional unit.  Ecosystems will not sustain if they are imbalance.  However, thare are many human activities, especially tourist activities lead to major implications on biodiversity of natural vegetation in Sulawesi. This paper presents informations and data on vegetation biodiversity and information about tourist activities in maintaining vegetation biodiversity. There are 57 endemic plant species in Sulawesi are still maintained and preserved. Most are in Gorontalo about 16 species, in North Sulawesi about 13 species, in Southeast Sulawesi 10 species, in Central Sulawesi 9 species and in South Sulawesi, 9 species. Activities carried tourists in maintaining diversity of species include: planting trees, learning and research the endemic species of plants and animals, and collect solid wastes in the tourism areas. These activities suggest a positive impact on the sustainability of forest ecosystems and economic benefits for the local communities. Keyword :Tourist activities,  biodiversity, endemic species.